Kewirausahaan Sosial Pada Pondok Pesantren Sidogiri Pasuruan - Azel Raoul Reginald; Imron Mawardi (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
Joblessness and lack of social welfare are economic problems which require the involvement of all people to overcome. The education aspect which functions to prepare educated human resource also plays important roles in reducing the level of joblessness and increase the social welfare. Islamic Boarding School Sidogiri Pasuruan as an educational institution not only provides Salaf education materials, but gives social benefits through its social entrepreneurship program.The aim of this research is to discover the social entrepreneurship applied at Islamic Boarding School Sidogiri Pasuruan. This research uses qualitative descriptive approach, by using a qualitative research of case study. Technique of data collection applied in this research is through documents, interview, participatory observation, and documentation upon the informants selected by using purposive sampling methods.The results of the research show that the application of social entrepreneurship at Islamic Boarding School Sidogiri Pasuruan can be proven by the innovation of establishment of social entrepreneurship institution, i.e. Kopontren Sidogiri (Cooperative of Islamic Boarding School Sidogiri), Pustaka Sidogiri, Buletin Sidogiri (Sidogiri Buletin), BMT Maslahah, BMT UGT Sidogiri, BPRS UMMU Sidogiri dan Koperasi Agro Sidogiri (Sidogiri Agribusiness Cooperative). They have been established based on the ideas and roles of civil society of Islamic Boarding School Sidogiri Pasuruan to maintain the economic activities, i.e. the duty of delivering Islamic values (dakwah), business, and providing social values for the society around Islamic Boarding School Sidogiri Pasuruan. REFERENCESBadan Pusat Statistik. 2013. Keadaan Ketenagakerjaan Februari 2013. Berita Resmi Statistik No. 35/05/Th. XVI, 6 Mei 2013.Departemen Agama Republik Indonesia. 2009. Al-Qur’an dan Terjemahannya. Jakarta: PT. Sigma Examedia Arkanleena.Hadits Riwayat Muslim, Tirmidzi dan AnNasa’i serta terjemahannya.Herdiansyah, Haris. 2010. Metodologi Penelitian Kualitatif untuk IlmuIlmu Sosial. Jakarta: Salemba Humanika.Hulgard, Lars. 2010. Discourses of Social Entrepreneurship-Variation of The Same Theme? EMES European Research Network.Juwaini, Ahmad. 2011. Social Enterprise Transformasi Dompet Dhuafa menjadi World Class Organization. Jakarta Selatan: Expose (Mizan Group).Mair, Johanna dan Ignasi Marti. 2006. Definisi Kewirausahaan Sosial. Dalam Minako Sakai dan Kacung Marijan (Ed.), Mendayagunakan Pembiayaan Mikro Islami (hlm. 3). Australia: Crawford School of Economics and Government, Australian National University.Mawardi, Imron dan Muhammad Nafik HR. 2011. Business Network of Pesantren and Its Mashlahah (Case Study in PP Sidogiri Pasuruan East Java). Universitas Airlangga: Departemen Ekonomi Syariah.Naji, A. Saifulloh, dkk. 2012. “Pesantren Harus Mandiri”. Tamassya (Laporan Tahunan Pengurus Pondok Pesantren Sidogiri) 1432- 1433H. Edisi 10. Pasuruan: Sekretariat Pondok Pesantren Sidogiri. . 2013. “Babak Baru Pendidikan Usia Dini”. Tamassya (Laporan Tahunan Pengurus Pondok Pesantren Sidogiri) 1433-1443H. Edisi 11. Pasuruan: Sekretariat Pondok Pesantren Sidogiri.Priyanto, Sony Heru. 2009. “Mengembangkan Pendidikan Kewirausahaan di Masyarakat”. Andragogia-Jurnal PNFI, 1 (1): 57- 82.Qomar, Mujamil. 2005. Pengertian Pondok Pesantren. Dalam Basori Vadlan (Ed.), Hubungan antara Kelekatan Santri pada Ustadz dengan Motivasi Belajar Santri di Pondok Pesantren Assalafiyah Mlangi Nogotirto Gamping Sleman Yogyakarta. Skripsi tidak diterbitkan (hlm.19). Yogyakarta: Fakultas Tarbiyah UIN Sunan Kalijaga.Qozazirin, Azhar, dkk. 2008. Buku Panduan Guru: Kewirausahaan Sosial Berbasis Sekolah. Indonesia: British Council.Rahmat, Abdul. 2011. “Pendidikan Berwawasan Kewirausahaan pada Usia Dini”. Jurnal Pedagogika, Vol. 2 No. 1 Hal: 1. Universitas Negeri Gorontalo: Jurusan Pendidikan Luar Sekolah.Sakai, Minako dan Kacung Marijan (2008), Mendayagunakan Pembiayaan Mikro Islami.Australia: Crawford School of Economics and Government, Australian National University.Saputro, Maryono Nanang. 2012. Daftar HIPSI, (Online), (http://pesantrenmandiri.com/?p age_id=1492, diakses tanggal 27 September 2012).Sriharini. 2003. Pondok Pesantren dan Pemberdayaan Ekonomi Masyarakat. Yogyakarta: Jurnal PMI Media Pemikiran Pengembangan Masyarakat.Walsh, Mayra. 2001. Pondok Pesantren dan Ajaran Golongan Islam Ekstrim (Studi Kasus di Pondok Pesantren Modern Putri “Danur Ridwan” Parangharjo Banyuwangi). Malang: Studi Lapangan ACICIS Program Fakultas Ilmu Sosial dan Politik Universitas Muhammadiyah Malang.Yin, Robert K. 2012. Studi Kasus: Desain dan Metode. Edisi 1 Cetakan ke11. Jakarta: Rajawali Pers.